2011
DOI: 10.1021/bi200644c
|View full text |Cite
|
Sign up to set email alerts
|

A Protein Arginine N-Methyltransferase 1 (PRMT1) and 2 Heteromeric Interaction Increases PRMT1 Enzymatic Activity

Abstract: Protein arginine N-methyltransferases (PRMTs) act in signaling pathways and gene expression by methylating arginine residues within target proteins. PRMT1 is responsible for most cellular arginine methylation activity and can work independently or in collaboration with other PRMTs. In this study, we demonstrate a direct interaction between PRMT1 and PRMT2 using co-immunoprecipitation, bimolecular fluorescence complementation, and enzymatic assays. As a result of this interaction, PRMT2 stimulated PRMT1 activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 66 publications
6
49
0
Order By: Relevance
“…Figure 2b displays the MS 2 of sDMA (top) and the MS 3 derived from the primary product ions 158.1 m/z (middle) and 172.0 m/z (bottom). As observed previously, the MS 2 for sDMA and aDMA are similar except for the unique product ions 46 m/z for aDMA and 172.1 m/z for sDMA (Rappsilber et al 2003;Brame et al 2004;Gehrig et al 2004;Lakowski and Frankel 2009;Lakowski et al 2010b;Pak et al 2011). The MS 3 spectrum of the primary product ion 172.2 m/z is diagnostic for sDMA (Fig.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Figure 2b displays the MS 2 of sDMA (top) and the MS 3 derived from the primary product ions 158.1 m/z (middle) and 172.0 m/z (bottom). As observed previously, the MS 2 for sDMA and aDMA are similar except for the unique product ions 46 m/z for aDMA and 172.1 m/z for sDMA (Rappsilber et al 2003;Brame et al 2004;Gehrig et al 2004;Lakowski and Frankel 2009;Lakowski et al 2010b;Pak et al 2011). The MS 3 spectrum of the primary product ion 172.2 m/z is diagnostic for sDMA (Fig.…”
Section: Resultssupporting
confidence: 78%
“…An MRM assay was used for the simultaneous quantification of aDMA, [Cθ1D 3 , Cθ2D 3 ]aDMA, sDMA, [Cθ1D 3 , Cθ3D 3 ]sDMA, histidine, and MMA (total) (Supplemental Table 1). The methods for detection of undeuterated methylarginines and histidine were described previously (Lakowski and Frankel 2009;Pak et al 2011). The method of quantification of δMMA and ηMMA using MRM 3 is described elsewhere (Lakowski et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, not only have PRMTs been shown to homooligomerize, but some studies support the possibility that PRMTs in mammals and plants have the ability to form heteromers. For example, mammalian PRMT2 can interact with PRMT1 both in vivo and in vitro, T. brucei PRMT Is an Enzyme-Prozyme Pair FEBRUARY 10, 2017 • VOLUME 292 • NUMBER 6 although the extent to which this occurs in vivo is unknown (60). Interestingly, recombinant PRMT2 enhanced the activity of recombinant PRMT1 up to 15-fold even when PRMT2 harbored inactivating mutations, suggesting a possible regulatory role for PRMT2.…”
Section: Promentioning
confidence: 99%
“…The active-site residue D51 is thought to play a role in a catalytic His-Asp dyad for deprotonation of the substrate arginine guanidino group, and E153 is positioned to form hydrogen bonds to the arginine guanidino group. [19,20] D51R and E153Q have previously been shown to abolish enzyme activity, [19,[21][22][23][24] and it has been proposed that D51 and H293 might form a structurally important dyad. [23] We found that D51N PRMT1 was less active toward the peptide series as a whole than wild-type PRMT1, yet this enzyme variant was most active toward R1-OH and R1-CH 3 .…”
Section: Methylation Of the R1 Series Of Peptidesmentioning
confidence: 99%
“…[15] 14 C Methylation and tricine gel separation of the R1 peptide series: Enzymes were prepared as previously described. [15,22,25,36] The PRMT1 D51N variant was created from pET-28(+)-PRMT1 using QuikChange (Agilent Technologies) and primers D51N-F (5'-CCA CGA GGA GAT GCT AAA GAA TGA G-3') and D51N-R (5'-CGT GAG GGT TCG CAC CTC ATT CTT TA-3'). R1 peptide (250 mm) was incubated in methylation buffer (HEPES (50 mm pH 8.0), NaCl (10 mm), dithiothreitol (DTT, 1 mm)) [25] with S-adenosyl-l-[methyl- ), and PRMT1, PRMT4, PRMT6, PRMT1 E153Q, or PRMT1 D51N (2 mm) for 16 h at 37 8C.…”
mentioning
confidence: 99%